The training of neonatologists and the paradigms implied in their relationship with the parents of babies in the Neonatal Intensive Care Unit - Ethel Cukierkorn Battikha; Maria Teresa de M. Carvalho; Benjamin Israel Kopelman (Sociedade de Pediatria de São Paulo, 2014)
Objective: To analyze and to interpret the psychological repercussions generated by the presence of parents in the Neonatal Intensive Care Unit for residents in Neonatology. Methods: Study based on the psychoanalytic theory, involving a methodological interface with qualitative surveys in Health Sciences. Twenty resident physicians in Neonatology, from five public institutions of São Paulo state, responded to a single semi-structured interview. Based on several readings of the material, achieving the core of emergent meanings that would be significant to the object of the survey, six categories were elected for analysis and interpretation: parents' staying at the Neonatal Intensive Care Unit and its effects on the neonatologists' professional practice; communication of the diagnosis and what parents should know; impasses between parents and doctors when the diagnosis is being communicated; doctor's identification with parents; communication of the child's death and their participation in the interview. Results: The interpretation of the categories provided an understanding of the psychic mechanisms mobilized in doctors in their relationships with the children's parents, showing that the residents experience anguish and suffering when they provide medical care and during their training process, and also that they lack psychological support to handle these feelings. Conclusions: There is a need of intervention in neonatologists training and education, which may favor the elaboration of daily experiences in the Unit, providing a less anguishing and defensive way out for young doctors, especially in their relationship with patients and parents.